2021
DOI: 10.1016/j.cjtee.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preperitoneal pelvic packing for hemodynamically unstable patients with pelvic fractures

Abstract: Purpose Hemodynamically unstable patients with pelvic fractures still represent a challenge to trauma surgeons and have a very high mortality. This study was designed to explore the effect of the interventions of direct preperitoneal pelvic packing for the hemodynamically unstable pelvic fractures. Methods This retrospective study enrolled 67 cases of severe pelvic fractures with unstable hemodynamics from October 2011 to December 2019. All patients presented in our eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…In addition, the need for transfusions after EPP and in the next 24 hours decreased 5,9,10,12,21,26,28,29 . In our series, patients who died received significantly more blood products.…”
Section: Multivariate Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the need for transfusions after EPP and in the next 24 hours decreased 5,9,10,12,21,26,28,29 . In our series, patients who died received significantly more blood products.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Other studies that published their experience with EPP [5][6][7]9,10,[12][13][14][15][16]21,[26][27][28][29] also reported a high mean ISS, between 30 and 55, though with lower mortality, ranging from 7.14% to 36.3%. Cheng et al 6 reported 61% of patients with extrapelvic lesions with AIS ≥4, while Burlew et al 5 reported that 85% of patients required other surgical procedures (on average, three procedures in addition to EPP and pelvis EF), with a mean ISS of 48.…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando estudos que publicaram suas experiências com TXP 5,7,9,10,[12][13][14]21,26,28,29 , exceto o estudo publicado por Cheng et al 6 , todos apresentaram maior média de unidades transfundidas antes do TXP, variando de 3,7 a 12 unidades de CH. Além disso, essas transfusões ocorreram em menos tempo, variando de 22 (±8) minutos a 82 (±13) minutos, exceto no estudo publicado por Totterman et al 14 .…”
Section: Análise Multivariadaunclassified
“…A maior quantidade de CH recebida em menos tempo antes do TXP provavelmente resultou na melhora da perfusão tecidual e no controle do sangramento em um estágio anterior, antes do desenvolvimento da coagulopatia. Além disso, a necessidade de transfusões após o TXP, e nas próximas 24h, diminuiu 5,9,10,12,21,26,28,29 .…”
Section: Análise Multivariadaunclassified